Intervention effect of physical activity on motor coordination in children and adolescents with developmental coordination disorder: a meta-analysis - Hua, Lijun; Song, Zhenpeng; Liu, Jiao; Zhang, Bin (Frontiers in Psychology, 2025)
ObjectivesThis review aims to explore the effects of physical activity on improving motor coordination in children and adolescents with developmental coordination disorders.MethodsDatabases such as PubMed, Web of Science, Embase, Cochrane Library, CINAHL, and SPORTDiscus were searched according to the PRISMA framework. A total of 9 studies involving 543 participants aged 5-16 years were included. Physical activity intensity, duration of each session, weekly frequency, and total intervention cycle were set as moderating variables for subgroup analysis by Revman5.4 and Stata16 software.Results(1) Meta-analysis showed no statistically significant improvement in motor coordination with physical activity interventions, as measured by either the MABC (MD = −0.49, 95% CI: −1.44 to 0.46, p = 0.31) or the MABC-2 (MD = 2.97, 95% CI: −2.25 to 8.18, p = 0.26) scale. (2) Subgroup and sensitivity analyses indicated notable heterogeneity across studies, which was potentially related to variations in the intervention parameters and control group conditions. While low-intensity activities appeared to show a favorable trend, this finding should be interpreted with caution, given the limited number of studies and differences in study design.ConclusionBased on the current limited evidence, physical activity did not yield a uniform improvement in motor coordination among children and adolescents with developmental coordination disorders. However, variations in the study design, including differences in intervention intensity and control group activity, may contribute to the observed inconsistencies. Future studies with larger, well-controlled, randomized trials are needed to clarify the specific conditions under which physical activity may exert optimal benefits.